Functional and genomic characterization of Pediococcus pentosaceus NR4-4 reveals a safe bacteriocinogenic probiotic with strong anti-listerial activity and prebiotic metabolism - Natnarin Ratthanachot; Weerapong Woraprayote; Thitiphorn Janyaphisan; Somboon Tanasupawat; Duangjai Ochaikul; Jaruwan Sitdhipol; Sukanya Phuengjayaem; Saranporn Poothong; Worasan Charunanthasunthon; Thitirat Buahom; Engkarat Kingkaew (Journal of Agriculture and Food Research, 2026)
The growing interest in bacteriocin-producing lactic acid bacteria from traditional fermented foods has highlighted the value of strains that combine antimicrobial activity, probiotic functionality, and genome-supported safety. This study presents an integrated functional and probiogenomic characterization of Pediococcus pentosaceus NR4-4 isolated from Thai fermented mustard greens. The strain was found to produce a heat-stable class IIa bacteriocin with pronounced inhibitory activity against Listeria monocytogenes . In addition, NR4-4 exhibited strong tolerance to simulated gastrointestinal conditions and demonstrated effective adhesion to Caco-2 intestinal epithelial cells. In vitro safety evaluations confirmed that the strain was non-hemolytic and did not exhibit cytotoxic effects toward AGS or Caco-2 cell lines. Whole-genome sequencing verified species identity and revealed the presence of pediocin-related gene clusters, carbohydrate-active enzymes associated with fructooligosaccharide utilization, and a favorable genome-based safety profile. Notably, no virulence factors, biogenic amine biosynthesis pathways, plasmids, or transferable antimicrobial resistance determinants were detected. The preferential metabolism of fructooligosaccharides further suggests compatibility with synbiotic formulations. Overall, these findings indicate that P. pentosaceus NR4-4 is a genomically supported, safe, and multifunctional probiotic candidate with potential applications in food biopreservation and functional food development. • Pediococcus pentosaceus NR4-4 produces a heat-stable pediocin-like bacteriocin with strong activity against Listeria monocytogenes. • The strain exhibits high tolerance to simulated gastrointestinal conditions and strong adhesion to intestinal epithelial cells. • Strain NR4-4 preferentially metabolizes fructooligosaccharides, supporting its synbiotic compatibility. • Genome-based analysis confirms the safety of NR4-4 and the absence of virulence-associated genes.
Keywords: Probiotics and Fermented Foods; GABA and Rice Research; Gut microbiota and health